The poetic priestly source - Gaines, Jason M. H. (Minneapolis, Fortress Press, 2015)
Much of scholarly research on the Pentateuch has revolved around the question of sources and how they might be identified by differences in vocabulary, theme, and characterization. Jason M.H. Gaines brings a different perspective to the delineation of the Priestly source (P) by applying specific criteria for the identification of biblical Hebrew poetry. These criteria allow him to distinguish a nearly complete poetic P stratum ("Poetic P"), coherent in literary, narrative, and ideological terms, from a later prose redaction ("Prosaic P"), which is fragmentary, supplemental (filling out mundane details including names dates, ages, places, numbers, and so on), and distinct in thematic presentation and apparent theological concern. Gaines describes the whole of the "Poetic P" source and offers a Hebrew reconstruction of the document. He also outlines the different emphases of the two strata, including differences in the characterization of patriarchs and of God's treatment of a disobedient Israel. The result is a coherent and dramatically innovative understanding of the history of the Priestly composition that is sure to draw keen interest and to open up new vistas in the study of the Pentateuch.
1. Identifying poetic features in Biblical texts -- 2. Differentiating poetic and prosaic texts -- 3. Poetic elements in priestly narrative -- 4. Poetic and prosaic strata in Genesis 6-9 -- 5. The priestly source in scholarship -- 6. Preliminary divisions between poetic and prosaic priestly strata.
"This book is a significant revision of my 2013 PhD dissertation, Poetic Features in Priestly Narrative Texts, written at Brandeis University in Waltham, Massachusetts"--Page xi.
Includes bibliographical references (pages 468-507) and indexes.
Includes Hebrew text.
Keywords: Bible. -- Criticism, interpretation, etc; P document (Biblical criticism); Hebrew poetry, Biblical -- History and criticism; Criticism, interpretation, etc